Validation of the polled celtic variant in south african bonsmara and drakensberger beef cattle breeds - (:unkn) unknown (My University, 2018)
An increased awareness of animal welfare necessitates the breeding of genetically polled animals, especially since more than 70% of South African beef cattle are rounded off in commercial feedlots. The Bonsmara and the Drakensberger, two locally developed breeds, play a major role in beef production in South Africa. The causative mutation for polledness in these breeds have not been confirmed, therefore, this study aimed to validate the POLLED Celtic variant as the causative mutation of polledness in the South African Bonsmara and Drakensberger beef cattle breeds. A total of 386 animals, consisting of Bonsmara, Drakensberger and Herefords (included as a Bos taunts control), were tested for the Celtic mutation by PCR-based screening. Phenotypically polled and scurred animals were found to carry at least one copy of the Celtic allele (P-c ) whereas homed animals were homozygous wild type. The highest frequency of homozygous polled animals (P-c/P-c = 0.337) was observed in the Bos taunts control (Hereford breed) while the majority of the Bonsmara animals were heterozygous polled (P-c/P = 0.591). For the Drakensberger, a heterozygous (P-c/p) genotypic frequency of 0.346 was observed, with the majority of animals being homed (p/p = 0.639). In the Bonsmara and Hereford breeds, a high proportion of heterozygous polled animals were phenotypically scurred, emphasizing the importance of correct phenotyping at farm level. This research validates the Celtic mutation as causative mutation for polledness in indigenous South African beef cattle breeds. It also demonstrates the current challenges with regards to both phenotypic and genetic verification of the scurs phenotype and requires further investigation in South African beef cattle breeds.
Keywords: African Research